Influence of Polysaccharides’ Molecular Structure on the Antibacterial Activity and Cytotoxicity of Green Synthesized Composites Based on Silver Nanoparticles and Carboxymethyl-Cellulose - María de los Ángeles Martínez-Rodríguez; Elizabeth Madla-Cruz; Victor H. Urrutia-Baca; Myriam A. de la Garza-Ramos; Virgilio A. González-González; Marco A. Garza-Navarro (Nanomaterials, 2020)
In this paper we report on the influence of polysaccharides’ molecular structure on the antibacterial activity and cytotoxicity of composites based on silver nanoparticles (AgNPs) immobilized into carboxymethyl-cellulose (CMC). These composites were green synthesized from the reduction of silver ions into aqueous solutions of the polysaccharide, using CMC with different degree of substitution (DS) and molecular weight (Mw). The composites were characterized by transmission electron microscopy (TEM), as well as infrared (ATR-FTIR), ultraviolet (UV-Vis), Raman, and X-ray photo-electron (XPS) spectroscopic techniques. The antibacterial activity was evaluated with minimum inhibitory concentration against Enterococcus faecalis. The cytotoxicity of composites was assessed against human gingival fibroblast. Experimental evidence suggests that particle size distribution and morphology of AgNPs change according to the quantity of silver precursor added to the reaction, as well as the DS and Mw of CMC used for composites preparation. This is related to the dispersion of silver precursor into aqueous solutions of the polysaccharide and the formation of Ag-O coordination bonds among AgNPs and COO− moieties of CMC. Moreover, these coordination bonds modify the ability of nanoparticles to produce and release Ag+ into aqueous dispersion, adjusting their antibacterial activity and the induction of cytotoxicity into the tested biological environments.